Cancer Therapeutics–related Cardiac Dysfunction in Patients Treated With Immune Checkpoint Inhibitors: An Understudied Manifestation. Issue 5 (11th June 2021) - Peleg Hasson, Shira; Arnold, Joshua; Merdler, Ilan; Sivan, Ayelet; Shamai, Sivan; Geva, Ravit; Merimsky, Ofer; Shachar, Eliya; Waissengrin, Barliz; Moshkovits, Yonatan; Arbel, Yaron; Topilsky, Yan; et al.
Abstract : The widespread use of immune checkpoint inhibitors (ICI) has become a mainstay of care for a variety of malignancies. However, these therapies portend a range of adverse effects, including a potentially fatal form of cardiotoxicity which to date has not been elucidated. We aimed to evaluate the baseline characteristics of ICI-mediated cardiotoxicity. We performed a retrospective study evaluating patients treated with ICI who performed at least 2 echocardiography examinations, before and after the initiation of ICI. Cardiotoxicity was defined as Cancer Therapeutics-related Cardiac Dysfunction (CTRCD) development, with an absolute left ventricular ejection fraction reduction of >10%, to a value <53%. Fifty-two patients were included with a male preponderance (65%) and a mean age of 66 (±12) years. Twelve (23%) patients developed CTRCD, of which 2 patients were diagnosed with myocarditis. Among the CTRCD group, patients tended to be older and more likely to have baseline diastolic dysfunction: lower e′ septal ( P =0.026), higher E/e′ septal ( P =0.035), and a trend of E/e′ average ( P =0.076). All-cause and cardiovascular hospitalizations were significantly more common among the CTRCD group ( P =0.028 and 0.001, respectively). Higher prevalence of cardiovascular mortality was observed among the CTRCD group (25% vs. 2%, P =0.034). We evaluated the development of CTRCD among patients treated with ICI therapies. Our findings suggest that baseline diastolic parameters may be associated with CTRCD development assisting in the early diagnosis of ICI-induced cardiac injury.